Woods from arid zones of Mexico, calorific power from TGA-DTA and calorimetric pump - Barrera-Calva, Enrique; González, Federico; Hernández-Pérez, Carlos David; Martínez, Gloria; Huerta-Arcos, Lázaro; Rosas-Cedillo, Ricardo; Rentería - Tapia, Víctor (Instituto de Ecología, A.C., 2021)
The calorific power of wood of huizache (Acacia farnesiana), maguey (Agave salmiana), nopal (Opuntia streptacantha), garambullo (Myrtillocactus geometrizans) and cardon (Pachycereus sp) from arid areas of Mexico, which are often used for heating water and cooking food in rural areas, in this work are presented. The calorific power determination was carried out by means a calorimetric combustion pump and of a gravimetric thermal analysis, GTA and differential thermal analysis technique, DTA, which is quite similar to the differential scanning calorimetry (DSC). In general, the results showed that the calorific value estimated by analysis (GTA-DTA) is in all cases slightly lower than those estimated with a calorimetric pump, but in general, both results are very close between each other. Maximum variation between these values is within ± 5%, which is associated in a range within the uncertainty of the measurements made. For the nopal wood, it was found that the calorific value, estimated by GTA-DTA, reaches (11 275 kJ/kg), resulting very similar to the value determined with a calorimetric pump, (11 605 kJ/kg). In the other cases studied a greater discrepancy between the measured values was found. The elementary analysis of the woods and their ashes estimated by means of X-ray photoelectron spectroscopy (XPS), allows the determination of the carbon intensity of the woods, and indicates that there is no evidence of toxic metals such as those from coal, which shows that these woods are a sustainable and renewable product, when they are available for combustion and heat energy obtainment.